Analysis of the Set of Trajectories of Fuzzy Equations of Perturbed Motion - Martynyuk, A. A.; Martynyuk-Chernienko, Yu. A.; Мартынюк, А. А.; Мартынюк-Черниенко, Ю. А.; Мартынюк, А. А.; Мартынюк-Черниенко, Ю. А. (Institute of Mathematics, NAS of Ukraine, 2014)
The paper presents a new approach to the investigation of the first-order fuzzy initial-value problems. We use different versions of the comparison principle to establish conditions for the existence of solutions of a set of differential equations.